Optimized endogenous lipid concomitants in flaxseed oil by different oil extraction technologies: Their positive roles in emulsions. (1st February 2022) - Cheng, Chen; Yu, Kun; Yu, Xiao; Geng, Fang; Huang, Fenghong; Wang, Lei; Huang, Qingde; Quan, Shuang; Deng, Qianchun
Abstract: In this study, different oil extraction technologies were used to obtain flaxseed oil with different lipid concomitants, and the influences of endogenous lipid concomitants on the stability and digestion properties of flaxseed oil emulsions were investigated. Compared with cold-press (CP), microwave pretreatment coupled with cold-press (MPCP) and accelerated solvent extraction (ASE) contributed to the accumulation of hydrophilic and lipophilic lipid concomitants, respectively. Subcritical fluid extraction (SFE) and supercritical CO2 extraction (SCO2 E) were conducive to the accumulation of amphipathic lipid concomitants. After emulsification, ASE-flaxseed oil emulsions had the lowest initial particle size due to the high content of amphiphilic lipid concomitants phospholipids. Phospholipids are spontaneously adsorbed on the interface of flaxseed oil and water. Antioxidative lipid concomitants (phenols, phytosterols, carotenoids, flavonoids, and cyclolinopeptides (CLs)) in MPCP-flaxseed oil improved the oxidative stability of emulsions. After digestion, ASE-flaxseed oil emulsion presented the highest FFAs% (∼78%) owing to smaller particle size. The release of FFAs decreased by 5%–10% in MPCP-, SCO2 E-, and SFE-flaxseed oil emulsions ascribed to the high content of phenols. In conclusion, MPCP and ASE are powerful flaxseed oil extraction technologies for improving the stability and digestion of emulsions, respectively. Graphical abstract: Image 1 Highlights: The methods of CP, MPCP, ASE, SCO2 E and ASE were used to extract flaxseed oil. Oil extraction methods influenced the content of lipid concomitants in flaxseed oil. SCO2 E-flaxseed oil emulsions were unstable for the prooxidative activity of FFAs. MPCP-flaxseed oil emulsion was stable for high content of tocopherols, flavonoids. ASE-flaxseed oil emulsions promoted FFAs release for its lower diameter size.